Relasi Kekuasaan dalam Novel Misteri Terakhir 1 dan Misteri Terakhir 2 Karya S. Mara Gd Serta Relevansinya terhadap Pembelajaran Sastra Berbasis Multikulturalisme di Sekolah Menengah Atas - Sahra Erika; Muhammad Rapi Tang; Sulastriningsih Djumingin (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This study is aimed at describing a form of power relation, resistance to the meaning of the power relation in S. Mara Gd’s novel Misteri Terakhir 1 and Misteri Terakhir 2 and their relevance to literature learning in SMA. This study used a descriptive method with a qualitative approach. Data collection technique used documentary method using documentation and note-taking techniques. The data analysis technique used is Miles and Hubeman, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that the form if power relations over the mind consist if stigmatization, control, manipulation, and objectivity. The form of resistance to representation of power are negotiation and resistance. The result of the analysis of the novels have potential to be a source of developing multiculturalism and character building in SMA because they teach about how a child obedient and devote to their parents.